Multidisciplinary management of impacted central incisors due to supernumerary teeth and an associated dentigerous cyst - Ritesh R Kalaskar; Ashita R Kalaskar (Wolters Kluwer Medknow Publications, 2011)
Supernumerary teeth are the most common developmental dental anomaly resulting from hyperactivity of dental lamina, dichotomy, environmental factor, or polygenetic process of atavism. Supernumerary teeth present classical oral complication such as impaction of adjacent teeth, crowding, diastema formation, rotation, displacement of teeth, and occlusal interference. A dentigerous cyst associated with anterior supernumerary teeth (mesiodens) is rare and accounts for 5% of all dentigerous cysts. The present case reports describe the successful management of the impacted permanent maxillary central incisor positioned high in the vestibule. A combination of surgical and orthodontic techniques was employed to improve treatment outcome with greater hard and soft tissue preservation and to prevent psychological problems. In the surgical phase, supernumerary teeth and dentigerous cyst were removed. Subsequently traction was employed by bonding bracket on the labial surface using closed and open eruption techniques. Successively, fixed orthodontic treatment was started to align permanent maxillary central incisors in an occlusal plane. Thus, combination of surgical and orthodontic method can be the treatment of choice over surgical extraction, implant placement, and surgical repositioning.